PENGARUH PEMBERIAN TIMBAL (Pb) DOSIS KRONIS SECARA ORAL TERHADAP PENINGKATAN PENANDA KERUSAKAN ORGAN PADA MENCIT - Setiawan, Abdul Malik (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2012)
Several kind of heavy metals that present in the environment are considered as toxic substance to human and animal. Lead (Pb) is one of Â heavy metals that increase in use for the last decade. Lead toxicity to human had wide influence in medical aspect, from nerve problem, bone metabolics disturbance until liver and renal failure. This experiment tried to found out the effect of cronic oral lead consupmtion to lead plasma rate in mice. Design of this experiment is true research experiment to test wheater there is an effect of oral lead consumption to acumulation ofÂ Â lead in blood plasma of mice. The dose devided to two kinds, medium dose (50 ppm) and high dose (100 ppm). The results show increase of lead accumulation in blood plasma of the mice compared to control group.